Invariance of Domain for Operators of Class AG(S+) - Adhikari, Dhruba R. (The Nepali Mathematical Sciences Report, 2016)
Let X be a real reflexive Banach space and X∗ its dual space. Let T : X ⊃ D(T) → 2X∗ An operator of class AG(S+), where G ⊂ X is open. An invariance of domain result for T is established. This result extends a similar result of Park for single-valued operators of type (S+). The Skrypnik’s topological degree theory is used, utilizing approximating schemes of mappings of class AG(S+), along with the methodology of a recent invariance of domain result by Kartsatos and the author.